Meningkatkan Hasil Belajar Fiqih Shalat Melalui Metode Diskusi di MTs Riyadlus Sholihin - Kiromah, Syafiatul; Nafisah, Aisatun; Ghufron, Muhammad; Prasetiya, Benny (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
The problem of low fiqh prayer learning outcomes at MTs. Riyadlus Sholihin encourages the need for innovation in learning methods. The discussion method was chosen as an approach to improve students' understanding of fiqh prayer material. This activity aims to improve student learning outcomes while fostering critical thinking and collaboration skills. The method used in this activity involves initial identification of problems through observation and interviews, implementation of discussion-based learning, and evaluation using learning outcomes tests and observation of student participation. The results showed a significant increase in student learning outcomes after the implementation of the discussion method. In addition, students showed active participation and a deeper understanding of the fiqh prayer material. The conclusion of this activity is that the discussion method is proven effective in improving fiqh prayer learning outcomes, especially at MTs. Riyadlus Sholihin. The recommendation from this activity is the application of similar methods in other materials or subjects to support the improvement of the quality of learning in schools